Клады и случайные находки вещей круга “древностей антов” в Среднем Поднепровье. Каталог памятников - Корзухина, Г.Ф. (Материалы по археологии, истории и этнографии Таврии, 1996)
This work includes the catalogue of things “Antiquities of the Antae” (7th cent.A.D.) in the Middle Dnieper region. The author widely used the archive funds of museums materials lost during the Second World War, materials from privât archives of Artamonov M.I. and Fedorovsky A.S. The catalogue includes the findspots, description, drawin, the place where it is Kept, publications.